An analytical model of through-thickness photopolymerisation of composites: Ultraviolet light transmission and curing kinetics. (15th June 2020) - Saenz-Dominguez, I.; Tena, I.; Sarrionandia, M.; Torre, J.; Aurrekoetxea, J.
Abstract: In this paper, a kinetic model able to predict the evolution of the through-thickness degree of cure of ultraviolet (UV) cured composites has been developed and validated. The kinetic model, which is based on the autocatalytic model, depends on the temperature of the composite and the absorbed intensity by the photoinitiators. This intensity is calculated by an optical model divided into discrete values of wavelength. As a result, the kinetic model considers the main factors of UV curing: the resin, reinforcement and thickness of the composite; the incident UV light spectrum; the absorbance range of photoinitiators and its consumption during the photopolymerisation. The main values of the model can be obtained by spectrometry and measuring the electric resistance of the composite during the whole UV curing process.